Evaluating credit default risk in P2P lending: a market maturity perspective - Fialho, Rita Serras Celorico da Silva (2022)
Dissertation presented as the partial requirement for obtaining a Master's degree in Statistics and Information Management, specialization in Information Analysis and Management